Efektivitas Pemanfaatan Poskesdes Di Desa Nunuka Kecamatan Bolangitang Timur Kabupaten Bolaang Mongondow Utara - Pudul, Nursia; Gobel, Lisda Van; Thalib, Tety (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This study was conducted to determine the Effectiveness of Utilization of Poskesdes in Nunuka Village, Bolangitang Timur District, North Bolaang Mongondow Regency. The research method used is descriptive with a qualitative approach. Data collection techniques by means of observation and interviews based on interview guidelines submitted to informants with a focus on research on Human Resources, Facilities and Infrastructure and Public Awareness. The results of the study concluded that the utilization of Poskesdes in Nunuka Village, Bolangitang Timur District, North Bolaang Mongondow Regency was not yet effective. This can be seen from the human resources or as a medical personnel there is only one person and has a work service at the Health Center making working hours not optimal, and public awareness is still lacking to come for treatment and sometimes choose to come to the Health Center directly or another doctor. It is recommended that there is an increase in human resources or health medical personnel so that Poskesdes can be opened with regular working hours to make local people come for treatment and socialization is held to the community to utilize the Poskesdes that has been provided as a place to get health services that are easy to reach when they have health complaints or want to seek treatment.